The role of metabolic reprogramming in pancreatic cancer chemoresistance - Liu, Chang; Li, Changfeng; Liu, Yuanda (Frontiers in Pharmacology, 2023)
Pancreatic cancer is characterized by hidden onset, high malignancy, and early metastasis. Although a few cases meet the surgical indications, chemotherapy remains the primary treatment, and the resulting chemoresistance has become an urgent clinical problem that needs to be solved. In recent years, the importance of metabolic reprogramming as one of the hallmarks of cancers in tumorigenesis has been validated. Metabolic reprogramming involves glucose, lipid, and amino acid metabolism and interacts with oncogenes to affect the expression of key enzymes and signaling pathways, modifying the tumor microenvironment and contributing to the occurrence of drug tolerance. Meanwhile, the mitochondria are hubs of the three major nutrients and energy metabolisms, which are also involved in the development of drug resistance. In this review, we summarized the characteristic changes in metabolism during the progression of pancreatic cancer and their impact on chemoresistance, outlined the role of the mitochondria, and summarized current studies on metabolic inhibitors.